Slant null scrolls in Minkowski 3-space E_1^3 - Önder, Mehmet; Kaya, Onur (Kuwait Journal of Science, 2016)
In this study, we introduce a new type of null scrolls called slant null scrolls in Minkowski 3-space E_1^3. We define three types of slant null scrolls called alpha-slant, beta-slant and gamma-slant null scrolls and give characterizations for a null scroll to be a slant null scroll. We also give some characterizations for beta-slant B-scrolls. Moreover, for beta-slant null scrolls, we obtain some nonlinear differential equations and we give some results by using their analytical solutions. Finally, we give some examples for the obtained results.